PENGARUH HARGA PAKAN DAN BIAYA TENAGA KERJA TERHADAP PENDAPATAN USAHA AYAM RAS PETELUR DI YUSUF FARM - Pujo Wibowo; Nafik Umurul Hadi (Jurnal Cita Ekonomika, 2023)
Laying hens are one of the poultry commodities that have an important role as egg producers to support the availability of affordable and easily available animal protein. Livestock development is also directed at improving the quality of production, increasing income, expanding employment opportunities and providing business opportunities for people in the region. rural. The aims of this study were To determine the effect of feed prices and labor costs on the income of laying hens at Yusuf Farm, Kebonsari Village, Kademangan District, Blitar Regency. This research uses positivistic / quantitative with a descriptive approach. The test uses primary data. The population in the research that will be carried out by this researcher is all workers at Yusuf Farm, with the saturated sampling method. Data collection techniques use questionnaires. The data analysis tool used is Partial Least Square (PLS). The results of this study indicate that based on the evaluation results of the measurement model that the variables X1, X2 and Y a total of 10 indicators are declared valid. Based on the results of hypothesis testing, the variable price of feed and labor costs have a significant effect on the latent variable of income.